DAPK3 is Essential for DBP‐Induced Autophagy of Mouse Leydig Cells - Si Yang; Ying Yang; Linlin Xu; Chaoju Hao; Jiaxiang Chen (Advanced Science)
Abstract Dibutyl phthalate (DBP) has been widely used in the manufacture of various daily and industrial products. As one of the most important endocrine disruptors, DBP has male reproductive toxicity and can lead to testicular dysfunction. In view of the fact that Leydig cells are important functional and structural units in the testis, their damage will affect testicular function. However, the underlying mechanism of DBP‐caused damage to mouse Leydig cells remains elusive. In the study, it is confirmed that DBP can promote the expression of death‐associated protein kinase 3 (DAPK3), thereby inducing autophagy of mouse Leydig cells by using in vivo and in vitro experiments. Also, bioinformatics analysis and molecular biology experimental techniques are utilized to further demonstrate that DBP‐induced upregulation of DAPK3 results from both the activated transcription by specific protein 2 (Sp2) and the decreased ubiquitination and degradation by parkin RBR E3 ubiquitin‐protein ligase (PRKN). Interestingly, melatonin can inhibit both Sp2/DAPK3 and PRKN/DAPK3 signaling pathways by inhibiting oxidative stress, thereby alleviating DBP‐induced autophagy of mouse Leydig cells. Overall, the study unravels a novel regulatory mechanism of DBP‐induced autophagy of mouse Leydig cells and identifies DAPK3 as a potential therapeutic target for DBP‐caused damage to the male reproductive system.